2016
DOI: 10.1159/000441524
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socioeconomic Status and Ethnicity on Melanoma Presentation and Recurrence in Caucasian Patients

Abstract: Objectives: The impact of ethnicity and the socioeconomic status (SES) among Caucasians is not well studied. Here, we examine the impact of income on melanoma presentation and prognosis within a Caucasian cohort, accounting for ethnicity, as some reports suggest increased melanoma incidence in Ashkenazi Jewish (AJ) BRCA mutation carriers. Methods: We studied prospectively enrolled primary melanoma patients at New York University. SES data were estimated using United States' Census Bureau data and patient zip c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
3
9
1
Order By: Relevance
“…Surprisingly, we note that income quartiles within our cohort are significantly above nationwide median income, which may be in accordance with previous studies showing an increasing rate of developing skin cancer with higher incomes or educational level [ 20 , 24 , 25 , 26 ]. Some have attributed social trends such as perceptions of tanned skin and increased outdoor activity as historical correlations [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, we note that income quartiles within our cohort are significantly above nationwide median income, which may be in accordance with previous studies showing an increasing rate of developing skin cancer with higher incomes or educational level [ 20 , 24 , 25 , 26 ]. Some have attributed social trends such as perceptions of tanned skin and increased outdoor activity as historical correlations [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…We showed that lesions of the head and neck region, lower income quartiles, and African American race are associated with higher short-term and long-term mortality. Although our data indicates that lower median income predicts shorter survival, correlating with other types of skin cancer [ 18 , 19 , 20 , 21 ], modes of subsequent treatment were not significantly different with univariate analysis of race or income level. This intriguing finding could be confounded by the overall predilection of MCC towards Caucasian patients, potentially resulting in inadequate sample size effects for lower socioeconomic patients.…”
Section: Discussioncontrasting
confidence: 70%
“…However, average UV index alone is unlikely to account for the differences in incidence. Ethnicity, race, occupational exposures, recreational activities, socioeconomic status, genetics, and prevalence of sunscreen use are other factors that have been shown to influence the risk of developing melanoma. Although the UV index may correlate with incidence on a population level, histologic evidence of sun damage would be a more direct way to account for the regional differences.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, factors such as socioeconomic status, insurance status, and facility type, which can vary between regions, should be accounted for in future studies. These factors not only have the potential to influence the quality of treatment melanoma patients receive, but also the degree to which patients have access to follow‐up care …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation